mukhayyo IMPLEMENTATION OF ELECTRONIC TEXTBOOKS IN SECONDARY SCHOOLS: WHAT TEACHERS NEED: IMPLEMENTATION OF ELECTRONIC TEXTBOOKS IN SECONDARY SCHOOLS: WHAT TEACHERS NEED - Aripova, Mukhayo (Журнал иностранных языков и лингвистики, 2022)
Teachers are often reluctant to accept and use these technologies in the classroom, despite the numerous advantages thereof. In environments where the use of e-textbooks are mandatory, such reluctance often manifests as using the software in a superficial way and job dissatisfaction. The objective of this study is to determine the needs of teachers when implementing e-textbooks. An interpretive case study was conducted at a secondary school in South Africa.